A4.3 Adipocytes Modulate the Phenotype of Macrophages through Secreted Lipids. (25th February 2013) - Klein-Wieringa, IR; Andersen, SN; Kwekkeboom, JC; Giera, M; Lange-Brokaar, BJE de; Osch, GJVM van; Zuurmond, AM; Stojanovic-Susulic, V; Nelissen, RGHH; Huizinga, TWJ; Kloppenburg, M; Toes, REM; et al.
Abstract : Background: Adipose tissue secretes a wide range of soluble factors that can influence whole body metabolism. Previous studies have shown an accumulation of macrophages and an enhanced pro-inflammatory profile of these cells in adipose tissue of obese mice. Modulation of macrophages by soluble mediators released by adipocytes has been proposed as a possible mechanism underlying these changes. In humans, an increased number of macrophages in adipose tissue of obese individuals have been observed, although no clear change in macrophages phenotype could be established. Moreover, no information exists about the interaction between macrophages and adipocytes in humans. Objective: In the present study, we explored the possibility that adipocytes modulate the phenotype of macrophages and studied the possible molecular pathways involved in this modulation. Results: Treatment of macrophages with adipocyte-conditioned medium (ACM) resulted in a strong reduction in IL-12p40 secretion upon LPS stimulation, whereas TNFα and other cytokines remained largely unaffected. This effect was independent of the source of ACM. Interestingly, the inhibition increased with increase in Body Mass Index (BMI) of the adipocyte donor. Therefore, it was hypothesised that the effect is mediated by a soluble factor whose release is correlated to the BMI of the adipocyte donor. To this end, we measured several cytokines, adipokines and lipids present in ACM. Among these, the release of several free fatty acids (FA) and PGE2 correlated with the BMI of the adipocyte donor. Further tests indicated that oleic and linoleic acid, as well as PGE2 were able to inhibit IL12p40 secretion, whereas palmitic acid could not. Upon separation of ACM protein and lipid fractions, we confirmed that inhibition of IL12p40 resides mainly in the ACM lipid fraction. Conclusions: These results provide first evidence that obesity-related changes in macrophage phenotype could be mediated by adipocytes in humans. These effects are mainly mediated through lipids released by adipocytes. Intriguingly, modulation appears different than in murine obesity, indicating that the immunomodulatory effects of obesity could be different in humans and mice.